Comparison of cardiac dysfunction in thalassemia major patients using deferoxamine or deferiprone as an iron-chelating agent - Rosalina Josep; Pustika Amalia Wahidiiyat; Partini Trihono; Piprim Yanuarso (Indonesian Pediatric Society Publishing House, 2012)
Background In thalassemia major (TM) patients, major mortality is due to cardiac hemosiderosis. Several types of iron chelating agent available recently are given to overcome this problem Objective To compare cardiac dysfunction in thalassemia major patients who used subcutaneous deferoxamine (DFO) to those who used oral deferiprone (DFP) as an iron􀁆chelating agent. Methods This cross􀁆sectional study was held at the Thalassemia Center, Department of Child Health􀁆Cipto Mangunkusumo Hospital (DCH􀁆CMH), Jakarta. We included TM patients aged 1O􀁆18 years Mth a mean pre􀁆transfused hemoglobin level of 2:.7 g/dL in the prior year, and who had used DFO or DFP for at least 1 year v.ith good compliance, at a standard dose of DFO at 40-60 mg/kg/day for 5 days a week or DFP at 50-100 mg/kg/day. We excluded TM patients v.ith congenital heart disease or overt heart failure. Trans􀁆thoracal echocardiography was performed at the Integrated Cardiac Service, CMH by a pediatric cardiologist using the conventional method and tissue Doppler imaging (TD I) consecutively, and within 2 weeks of the subject's receiving a packed red blood cell (PREC) transfusion. The 57 TM subjects consisted of 19 DFO users and 38 DFP users. Results In our subjects, diastolic dysfunction was more commonly seen than systolic dysfunction, especially moderate diastolic dysfunction. In the DFO group, diastolic dysfunction only was detected in 3/19 subjects, systolic dysfunction only in 1/19 subjects, and both diastolic and systolic dysfunction in 15/19 subjects. None of the DFO users had normal cardiac function. In the DFP group, diastolic dysfunction only was seen in 6/38 subjects, and both diastolic and systolic dysfunction in 30/38 subjects, while 2/38 subjects had normal cardiac function. Conclusion Diastolic and/or systolic dysfunction was detected in the majority of subjects, but with preserved global cardiac function. We found that cardiac dysfunction was not significantly different in the two iron chelator groups. For all subjects, diastolic dysfunction  was seen in 89% of cases, while systolic dysfunction was detected in 77% of cases. [Paediatr Indones. 2012;52:272,9].